アスカ カンソク キョテン ト ショウワ キチ カン ノ ジュウリョク ケツゴウ オヨビ ルンドボークスヘッタ ニ オケル ジュウリョク ソクリョウ - 福田, 洋一; フクダ, ヨウイチ; Fukuda, Yoichi (1986)
P(論文) 第27次南極地域観測隊(JARE-27)の夏季観測の一環として, 1985年12月末から1986年1月初旬にかけて, あすか観測拠点と昭和基地間の重力結合を実施した。使用した重力計はラコステ重力計G-477およびG-805の2台である。今回の重力結合は, あすか観測拠点から昭和基地に向かう片道だけで実施されたため, データの解析にあたっては, JARE-27で実施されたその他の重力測定の結果も考慮し, ドリフトレートなどのパラメーターを決定するなど細心の注意を払った。その結果, あすか観測拠点の重力値は, 昭和基地との相対値として0.2mgal程度の精度で決定することができた。この精度は, 最近の精密重力結合の精度と比較して必ずしも満足のいくものではないが, 南極における種々の測定条件を考慮すると妥当なものである。一方, 1986年1月の下旬にリンドボークスヘッタにおいて, 同地域の重力異常を調べる目的で測地基準点など新たに8カ所の測定点で重力測量を実施した。その結果についても報告する。 Gravimetric connection between Asuka Camp and Syowa Station was established during the summer activities of the 27th Japanese Antarctic Research Expedition (JARE-27). Gravity measurements were carried out by using two LaCost & Romberg gravimeters model G (G-477 and -805) at Asuka Camp on December 27th and 28th, 1985,and also at Syowa Station in early January, 1986. Although the gravimetric connection was achieved only one way, data analyses were carried out successfully using all other gravity measurements during JARE-27 to detect drift rates and other instrumental parameters. The gravity values at Asuka Camp were relatively determined from the value at Syowa Station within the accuracy of 0.2 mgals. Although it is not satisfactory compared with the recent precise gravity measurements, the accuracy is reasonable considering rather hard situations of the gravity measurements in Antarctica. Another gravity survey was carried out on Rundvagshetta in late January, 1986. Eight gravity stations, including five triangulation stations, one astro-geodetic station and other points, were newly established in the area. The results of the survey were also reported breifly. departmental bulletin paper